2016
DOI: 10.4067/s0718-16202016000100003
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF FOLIAR APPLICATIONS OF A BIO-STIMULANT DERIVED FROM ALGAE EXTRACT ON THE PHYSIOLOGICAL BEHAVIOR OF LULO SEEDLINGS (Solanum quitoense CV. SEPTENTRIONALE)

Abstract: Cien. Inv. Agr. 43(1):25-37. Seaweed extracts are used as nutritional supplements, biostimulants, or biofertilizers in agriculture and horticulture to increase plant growth and yield. In this experiment, foliar applications of bio-stimulant derivate from seaweed extract were tested on plant growth, leaf gas exchange properties, and proline accumulation in lulo seedlings cultivated under greenhouse conditions. Lulo plants were split into four treatments: (i) plants with soil fertilizer; (ii) plants treated only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…The results of the present study coincided with those reported by [56] in tomato plants (S. lycopersicum L.) from inoculation with Rhizophagus irregularis, which generated between 7.10 and 7.70 sheets unlike the control, which generated 6.50 sheets. In relation to leaf development, the length of the leaves were up to 60 cm [57], while Ref.…”
Section: Number Of Leaves and The Leaf Areasupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the present study coincided with those reported by [56] in tomato plants (S. lycopersicum L.) from inoculation with Rhizophagus irregularis, which generated between 7.10 and 7.70 sheets unlike the control, which generated 6.50 sheets. In relation to leaf development, the length of the leaves were up to 60 cm [57], while Ref.…”
Section: Number Of Leaves and The Leaf Areasupporting
confidence: 92%
“…In our study, from the application of arbuscular mycorrhizae and DAP, the diameter of the stem was 27.25% greater than the control plants. Similar values were reported by [56] in tomato seedlings (S. lycopersicum L.) whose increased stem diameters ranged between 5.55 and 6.13 cm while the control showed a value of 4.88 cm.…”
Section: Plant Height and Stem Diametersupporting
confidence: 87%
“…Stomatal conductance (gs) was measured in both experiments at the end of each irrigation period (30,40,50,and 60 DAT) on the second fully expanded leaf from the upper part of the canopy using a steady-state porometer (SC-1; Decagon Devices Inc., Pullman, WA). Total plant transpiration (E) was estimated only for the experiment in pots on the same dates as gs using the gravimetric technique described by Díaz-Leguizamón et al (2016), which consists of measuring the difference in the weight of plants in their pots every 24 h.…”
Section: Leaf Gas Exchange Parametersmentioning
confidence: 99%
“…This trend could be due to the biological activity of algae extracts, which are especially attractive as a natural source of bioactive molecules that promote plant growth (Khan et al, 2009). When Díaz-Leguizamón et al, (2016) compared foliar and substrate applications of algae extracts (Ascophyllum nodosum) to Solanum quitoense, foliar application was the most effective, obtaining a greater number of leaves and foliar area. The generation of the number of leaves with both applications of seaweed via foliar and substrate can be due to its composition, consisting of organic matter and NPK in the available forms, which led to the optimal nutritional status of E. grandiflorum plants (Yagoub et al, 2012).…”
Section: Number Of Sheetsmentioning
confidence: 99%